Smoking status and changes in thyroid-stimulating hormone and free thyroxine levels during a decade of follow-up: The Tehran thyroid study - Hoda kadkhodazadeh; Atiyeh Amouzegar; Ladan Mehran; Safoora Gharibzadeh; Fereidoun Azizi; Maryam Tohidi (Babol University of Medical Sciences, 2020)
Background: Smoking can cause thyroid disorders; the aim of the present study was to investigate the association between smoking status and changes in thyroid hormone levels among adult males during a decade long follow-up of in the Tehran Thyroid Study (TTS). Methods: Data of 895 adult males (smokers=115, non-smokers=691, ex-smokers=89) participants of the TTS without any previously known thyroid disease were analyzed. To examine trends of changes in thyroid hormone levels in these three groups, generalized estimating equation models were used. The interaction between the smoking status and each phase of the study was checked in a separate model. Results: Age and BMI adjusted trends of free thyroxine (FT4) demonstrated a non-significant decrease in participants (P=0.121) and thyroid-stimulating hormone (TSH) gained a significant average increase value over time in the total population (adjusted marginal mean of TSH=1.15 mU/L in phase 1, vs. 1.75 mU/L in phase 4, P<0.0001). Of the three groups, non-smokers and ex-smokers showed statistically significant increases in TSH during the follow-up period, whereas the smoker group had lower increases in TSH levels, changes from phase 1 until phase 2 among smokers were 38.46%, vs 43.54% and 52.94% in the ex and non-smokers, respectively. Conclusion: TSH was lower and FT4 was higher in smokers compared with the other smoker groups, although TSH level shows no decreasing trend over time in this group. The increasing trend of TSH in smokers was similar to ex and non-smokers. No difference was seen in FT4 trends among the smoking groups.